ANALISIS PENGARUH PROMOSI TERHADAP LOYALITAS KONSUMEN DENGAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI - Thomas Wijayanto; Marjam Desma Rahadhini; Sumaryanto Sumaryanto (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
Marketing has an important role in the success of the company, especially in the face of competition, maintaining excellence and developing a business to always achieve profit. This study aims to determine the effect of promotion and trust on consumer loyalty in the Semanggi Printing Association. This study uses purposive sampling method, the population in this study is the consumers of Semanggi Printing Association as many as 100 respondents. Data collection method used: questionnaire. Data analysis techniques used validity test, reliability test, classic assumption test, multiple linear regression test and Sobel test. The results of the study concluded that there was a significant influence on promotion of trust, there was a significant influence of trust on consumer loyalty, there was a significant influence on promotion of consumer loyalty, there was an indirect influence of promotion on consumer loyalty mediated by trust. Suggestions in this study were: Semanggi increases consumer loyalty, it is necessary to pay attention to promotion and trust variables because these variables have a significant effect on consumer loyalty.Keywords: Promotion, Trust, Consumer Loyalty